Analisis Kelayakan Usaha Penangkapan Ikan dengan Jaring Rampus (Bottom Gill Net) di Desa Bandengan Kecamatan Mundu Kabupaten Cirebon, Jawa Barat - Dirja M.Si; Wana Ligar Anarki (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2021)
Research was conducted from March to May 2020 at Bandengan Village, Mundu District, Cirebon Regency, West Java. Bandengan Village is a village located on the outskirts of the panatai with the majority of the population being fishermen. The fishing gear used by the fishermen of Bandengan Village includes rampus nets (Bottom Gill Net). Based on the results of the financial analysis including business income analysis, revenue and cost balance analysis, business feasibility analysis, net present value, internal rate of return (IRR) and payback period, the analysis of business income was obtained Rp. 22,346,000, - income and cost balance analysis 1.79, business feasibility analysis with Net Benefit 2.92, with a discount rate of 13%, the value of the catch in years 1 to 10 is Rp. 50,736. 000, -, at the end of the fifth year the remaining machine value is Rp. 1,000,000, -, and at the end of the project value of Rp. 9.500.000, -, consisting of boats Rp. Rp. 2,500,000, -, rampus fishing gear of Rp. 500,000, -, and a machine of Rp. 1,000,000, -, in order to obtain a Net Present Value of Rp. 125,798,041, -, Internal Rate Of Return (IRR) 47.46% and pay back period of 2.86 years. Thus, the use of rampus net fishing gear in Bandengan Village, Mundu District, Cirebon Regency is feasible to be developed, in addition to the higher quality catch, it is also included in environmentally friendly fishing gear.